Changing writing/writing for change. Issue 2 (12th March 2021) - Beavan, Katie; Borgström, Benedikte; Helin, Jenny; Rhodes, Carl
Abstract: The political potential of unconventional and even transgressive forms of writing in management and organization studies has been invigorated in recent years through an explicit connection with feminist theories, ideas, and practices. The results have been a new wave of scholarship that brings together the personal, the political, and the theoretical as a means to intervene in masculine orthodoxy of organizational writing. This intervention seeks to change what and how we understand organizational phenomena, with an ultimate goal of transforming practice toward a more equal and egalitarian future. We introduce five papers that responded to a call to explore the intersections between change and academic writing, as well as an exploration of alternatives to dominant masculine academic writing styles. Such writing, we aver, might facilitate change not just in the academy, but also in organizations and by extension, society.